Professional Certifications Propelling the Project Economy - Lee, Chia Kuang (2022)
The concept of project economy has always been associated with the concept of turning ideas into reality, focusing on creating long-term values, and ensuring alignment to value streams through successful project completion. Nations all over the world are embracing new business practices, shifting organisational structures around project portfolios in order to provide greater flexibility to their stakeholders. The Project Economy has indeed arrived.